2023
DOI: 10.55705/cmbr.2023.384467.1095
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of women breast cancer

Abstract: Breast cancer, the most frequent disease in women worldwide, represents a significant public health concern on a global scale. Breast cancer was the most frequent type of cancer among Iraqi women in 2018, accounting for the highest percentage of malignant tumors in women. Breast cancer is a set of physiological and molecular heterogeneous diseases that begin in the breast. Advanced breast cancer with distant organ metastases is considered incurable with current therapies. Aside from new treatment improvements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…LncRNA-UCA1 improved cell proliferation in esophageal cancer as a ceRNA of Sox4 (28). SNHG5 regulated the proliferation and migration of gastric cancer cells via miR-32/KLF4 axis (29)(30)(31)(32). Based on this theory, we hypothesized that LINC00467 may also function as ceRNA in BC.…”
Section: Discussionmentioning
confidence: 95%
“…LncRNA-UCA1 improved cell proliferation in esophageal cancer as a ceRNA of Sox4 (28). SNHG5 regulated the proliferation and migration of gastric cancer cells via miR-32/KLF4 axis (29)(30)(31)(32). Based on this theory, we hypothesized that LINC00467 may also function as ceRNA in BC.…”
Section: Discussionmentioning
confidence: 95%
“…By similarities, VTA1 is also implicated in EGFR sorting and downregulation. The expression of VTA1 in LUAD and its prognostic significance, however, are yet unknown [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-tumor impact of anoikis is undeniable, and prior research has shown that it is still fundamentally a sort of apoptosis. Anoikis resistance is one of the critical elements that cannot be disregarded in the evolution of cancer, according to an increasing number of studies [40][41][42][43][44][45][46]. According to our GSVA research, oxidative stress, EMT, and energy metabolism make up the majority of anoikis resistance.…”
Section: Discussionmentioning
confidence: 99%